An Investigation of Concept Attainment Model on Learning Achievement in Biology in Public Secondary Schools in Kibwezi Sub-County, Kenya - Kaseke, Ndolo Francis; Muola, James (Research journali’s Journal of Education, 2019)
Biology performance in public Secondary Schools has been quite low compared to the other sciences. This has been attributed majorly on the nature of teaching methods used, the abstract nature of biology, and the teachinglearning resources. This study sought to investigate the effect of concept attainment model on learning achievement in biology in public Secondary Schools of Kibwezi Sub-County, Kenya. There is inadequate research done on the effect of concept attainment model in the teaching-learning process in the classroom situation especially in Kibwezi Sub-County schools. The objective of the study was to establish the extent to which concept attainment model influences the level of students’ understanding of biological concepts. The research was based on Burner’s learning theory and component display theory. The research used a quasiexperimental design. Simple random sampling method was used to select four schools out of 52 Co-educational schools. The sample size comprised of 244 students from the four schools. Piloting was done in one public coeducational school in Makindu Sub-County. Concept attainment test (CAT) constructed by the researchers was used to collect data. It had an estimated reliability coefficient of 0.7 established through the split-half method. This CAT was administered to an experimental and control groups before the intervention was done. Data was analyzed using descriptive statistics, t-test and ANOVA through the Statistical Package of Social Sciences (SPSS) version 24. The study shows that students taught using CAM scored better and had increased the levels of understanding of biological concepts than those taught using the traditional methods. Biology educators in colleges and universities should incorporate CAM in their teacher education programmes and make it part of their curriculum also biology education stakeholders should encourage CAM in their teaching
Keywords: Concept attainment; model; learning achievement; Biology